Vachellia bolei (Leguminosae, Mimosaceae) a possibly extinct coastal stenoendemic legume of southern India - Kumar, Krishnachandran Sampath; Kathiresan, Kandasamy; Arumugam, Senniappan (Phytotaxa, 2019)
Based on intensive literature survey, thorough herbaria consultations, and extensive field surveys (2012–2017) along the coast of Tamil Nadu, besides consulting experts and botanists to resolve the typification and nomenclatural issues, the discovery, nomenclature, lectotype, distribution, and the present status of the coastal stenoendemic legume, Vachellia bolei (syn. Acacia bolei), in southern India, is discussed here in detail. Clarification regarding the Lectotype of the taxon is made and the extinction of the species is reported.